Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1089/scd.2014.0321
|View full text |Cite
|
Sign up to set email alerts
|

Antiphotoaging Effect of Conditioned Medium of Dedifferentiated Adipocytes on Skin In Vivo and In Vitro: A Mechanistic Study

Abstract: Photoaging of skin occurs partially due to decreased synthesis and increased degradation of dermal collagen. Antiphotoaging therapy aims to counteract these effects. This study aimed to investigate whether secretory factors from dedifferentiated adipocytes (DAs) could alleviate photoaging in human dermal fibroblasts (HDFs) and in mice and to clarify the underlying mechanism. DAs were acquired and verified based on cellular biomarkers and multilineage differentiation potential. The concentrations of several cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“… 21 Dedifferentiated adipocytes may participate in functional regulation in the form of secretion by reprogramming cytokine expression (especially TGF-β1). 22 , 23 In this study, we utilized a whole-gene expression profiling array to explore the genes differentially expressed in the process of dedifferentiation. Overall, 693 genes were differentially expressed between the two groups, and hSDF-1α was the most differentially expressed gene between De-hUC-MSCs and hUC-MSCs.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Dedifferentiated adipocytes may participate in functional regulation in the form of secretion by reprogramming cytokine expression (especially TGF-β1). 22 , 23 In this study, we utilized a whole-gene expression profiling array to explore the genes differentially expressed in the process of dedifferentiation. Overall, 693 genes were differentially expressed between the two groups, and hSDF-1α was the most differentially expressed gene between De-hUC-MSCs and hUC-MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Another kind of adipose-derived cells that showed stem cell characterization is dedifferentiated adipocyte (DFAT), which has the proliferative ability, lineage redifferentiation potential, and pluripotent features [ 37 ]. Xu et al study showed that DFAT is also useful for photoaging skin due to secreting TGF- β 1 [ 38 ]. TGF- β 1 plays an important role in both ASCs and DFAT antiphotoaging effect.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration technique using an ultrafiltration unit with a 3‐kDa cutoff could be another limitation. Several studies have applied a technique for concentrating CM using ultrafiltration units . Most materials in CM, such as growth factors, cytokines, hormones, and genetic materials, could be concentrated.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have applied a technique for concentrating CM using ultrafiltration units. 16,32,33 Most materials in CM, such as growth factors, cytokines, hormones, and genetic materials, could be concentrated. However, materials under the 3-kDa cutoff, such as amino acids and nucleotides, were removed and not concentrated.…”
Section: Discussionmentioning
confidence: 99%